The Influence of The Entrepreneurs’ Background on Digital Startups Attaining Investment Milestones in Indonesia - Furqon, Dzulfikar Ahmad; Permana , Muhmmad Yorga; Komarudin, Nurul Amri (Indonesian Journal of Business and Entrepreneurship, 2023)
This study delves into the importance of knowledge and information integration within entrepreneurship and its impact on the growth of digital startups in Indonesia. Specifically, the research focuses on the human capital derived from college education and the work experiences of entrepreneurs. By examining the educational background and professional experience of 207 digital startup entrepreneurs’ in Indonesia, the study employs various regression techniques to analyze the data collected between February and June 2021. The findings reveal that entrepreneurs’ who pursued higher education abroad significantly increased their chances of securing higher levels of investment. On the other hand, factors such as discipline, education level, and prior work experience demonstrate limited influence. These results contribute to our understanding of the factors that drive digital startups to achieve different investment milestones, emphasizinag the varying effects of different types of higher education and professional experience. These insights can be valuable for evaluating entrepreneurship programs in higher education institutions and guiding initiatives like student exchange programs and overseas training to foster human resource development in entrepreneurship. By enhancing our knowledge of human capital, this study contributes to the existing body of research and informs strategies for nurturing successful startups in the digital industry. Keywords: digital startups, entrepreneurship, series funding, higher education, human capital